2021
DOI: 10.4069/kjwhn.2021.12.08
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and main effects of physical and depressive symptoms on quality of life in Korean women seeking care for rectal prolapse: a cross-sectional observational study

Abstract: Purpose: Rectal prolapse is still a relatively understudied medical condition, especially in women, whereas physical symptoms, depressive symptoms, and quality of life (QOL) in women with pelvic organ prolapse have been steadily studied. This study aimed to examine the interaction and main effects of physical and depressive symptoms on physical and mental QOL of women seeking care for rectal prolapse in Korea. Methods: Ninety-two women with rectal prolapse were recruited from a colorectal surgery clinic of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…In Drages’ study, it was shown that the subjective severity of prolapse, determined in the International Consultation on Incontinence Questionnaire—Vaginal Symptoms score, is connected with greater psychological distress [ 29 ]. Authors who focused on rectal prolapse also found a connection between subjective complaints in the CRADI 8 questionnaire and depressive symptoms [ 13 ]. The aforementioned outcomes stay in agreement with the current outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drages’ study, it was shown that the subjective severity of prolapse, determined in the International Consultation on Incontinence Questionnaire—Vaginal Symptoms score, is connected with greater psychological distress [ 29 ]. Authors who focused on rectal prolapse also found a connection between subjective complaints in the CRADI 8 questionnaire and depressive symptoms [ 13 ]. The aforementioned outcomes stay in agreement with the current outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of consensus regarding the extent to which prolapse-related symptoms have an impact on depression, anxiety, or sleep disorders. In a Korean study of patients with rectal prolapse, the relationship between depression and the patient’s quality of life was confirmed; however, the authors did not compare psychiatric symptoms with patients without PFDs [ 13 ]. The relationship between POP and mental symptoms seemed to be indirectly confirmed by the observations of Ai and colleagues, who showed a reduction in the intensity of these complaints in patients who received pessary therapy due to pelvic organ prolapse [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…PFDs negatively affect many aspects of the patient’s quality of life [ 10 , 11 , 12 ]. At the same time, it has been shown that surgical treatment of POP and urinary incontinence using different surgical methods improves patients’ quality of life in many aspects, especially as lower urinary tract, prolapse, and colorectal symptoms were concerned.…”
Section: Discussionmentioning
confidence: 99%